2001
DOI: 10.1055/s-2001-11272
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus-paracasei-Endokarditis bei einer 18-jährigen Patientin mit Trisomie 21, atrioventrikulärem Septumdefekt und Eisenmengerreaktion - therapeutische Probleme

Abstract: Endocarditis caused by lactobacilli is very rare and so far has been rarely published in adults with cardiac valve diseases especially after dental manipulations. Because of diagnostic and therapeutical problems we hereby report on one case of a female adolescent with Down's syndrome who did not undergo surgical correction of atrioventricular septal defect because of early development of Eisenmenger's syndrome. The onset was subacut and the diagnostic procedures were considerably delayed. Risk factors for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…We found that BPT appears to be reliable and useful across a wide range of intellectual disability levels in this population. Much like the Severe Impairment Battery (Schmidt, Wolter, Lenschow, & Kienast, 2001; Tariot et al., 2004), BPT has proven useful in adults with moderate AD. This nonverbal instrument appears to be sensitive to change over time and to have minimal floor and ceiling effects in the selected cohort of aging individuals with DS.…”
Section: Discussionmentioning
confidence: 99%
“…We found that BPT appears to be reliable and useful across a wide range of intellectual disability levels in this population. Much like the Severe Impairment Battery (Schmidt, Wolter, Lenschow, & Kienast, 2001; Tariot et al., 2004), BPT has proven useful in adults with moderate AD. This nonverbal instrument appears to be sensitive to change over time and to have minimal floor and ceiling effects in the selected cohort of aging individuals with DS.…”
Section: Discussionmentioning
confidence: 99%
“…In this particular bacterium, few cases have been reported as the cause of human infections. These include splenic abscess after rupture of mycotic aneurysm due to intravascular infection [20], endocarditis and purpura fulminans associated with liver abscess [21], and endocarditis with cardiac valve disease [22]. As far as we are aware, this is the second case report and the first in Japan of splenic abscess caused by L. paracasei.…”
Section: Discussionmentioning
confidence: 97%